Dampak program pengendalian dengue di Kabupaten Lombok Tengah - Annisa Ayu Zulfia; Nurul Paramaiswari; Adnanto Wiweko; Astri Ferdiana (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Dengue fever is a major public health problem in tropical countries like Indonesia. Previous research evaluating larval monitoring and dengue fever, particularly in rural areas, is limited. Purpose: To analyze the achievement of dengue control programs in rural areas. Method: This case study uses secondary data from the 2023-2024 surveillance report, focusing on Orok Solong Hamlet, Kabul Village, one of the working areas of the Batu Jangkih Community Health Center. Descriptive analysis was conducted on trends in dengue cases, house index, and larva-free rates compared to the national target (≥95%). Validation was conducted through a review of program documents and cross-sectoral reports. Results: The larva-free rate increased from 85% in 2023 to 97% in 2024 after strengthening periodic larva monitoring activities and routine mosquito nest eradication. The active involvement of two mosquito larvae monitoring cadres, along with support from the village government, village supervisory officer, and hamlet heads, contributed to increased community participation and the effectiveness of vector control. Dengue fever cases decreased to two cases by the end of 2024. Conclusion: The periodic mosquito larvae monitoring and 3M Plus mosquito nest eradication program effectively increased the mosquito larvae-free rate from 85% to 97% and reduced dengue fever cases in Orok Solong Hamlet. Success was influenced by consistent interventions, the role of mosquito larvae monitoring cadres, community surveillance, and cross-sector support. Suggestion: This strategy can be implemented in other areas with cross-sector support and requires further study with a broader research scope. Keywords: Dengue Hemorrhagic Fever (DHF); Larvae Free Rate; Mosquito Nest Eradication; Periodic Larvae Monitoring.